Factors that predispose to causing diseases of abortions in dairy cows: a review - Córdova Izquierdo, Alejandro; Xolalpa Campos, Víctor Manuel; Córdova Jiménez, Mary Silvia; Córdova Jiménez, Crisitian Alejandro; Guerra Liera, Juan Eologio (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen